PENGARUH PVA PADA PEMBUATAN PUPUK UREA SLOW RELEASE FERTILIZER PADA MATRIKS KITOSAN TERMODIFIKASI - Betari Marena; Sari Edi Cahyaningrum (Unesa Journal of Chemistry, 2024)
Slow Release Fertilizer can be made with organic or inorganic materials. Several materials have been compared in their properties to produce SRF membranes that have the most suitable properties to be made as SRF. In this study, SRF was made with chitosan-PVA-Urea-Ca materials with the aim of increasing the efficiency of urea fertilizer absorption by plants. The method used in making this SRF is the casting method, the membrane solution will be spread on a surface and the solvent will be evaporated so that a dry SRF membrane can be produced. The results of the study showed that the more PVA added, the degree of swelling can be increased, its elasticity can be increased, and its porosity can be reduced so that it can increase the efficiency of urea absorption by plants